Clinical pathway for patients with Chronic Myeloid Leukaemia: The Euriclea Project - Botti, Stefano; Gargiulo, Gianpaolo; Bombaci, Felice; Artioli, Giovanna; Cosentino, Chiara; Pignatelli, Adriana Concetta; Torino, Daniela; Lionetti, Maria Marcella; Samarani, Emanuela; Cappucciati, Lorella; Bordiga, Paola; Diodati, Antonella; et al. (Acta Biomedica Atenei Parmensis, 2017)
Background and aims: The use of Tirosine Kinase Ihnibitors (TKIs) for the treatment of Chronic Myeloid Leukemia (CML) has definitely represented a turning point in the treatment of the onco-hematological diseases. Over the years, the interest of physicians, nurses, patients and caregivers has increasingly focused on the aspects of the humanization of care, the management of side effects and on the full and constant therapeutic adherence. The aim of the project was to define patient-oriented care processes, based on a proactive approach that can fully respond to the new health needs of CML patients. Methods: A nursing expert Working Group (WG) was established. WG reviewed literature about CML patients assistance and then it was conducted a survey on organizational models for the treatment of CML patients, adopted by Italian haematologic and transplant centers. Finally, the main issues regarding CML patients care were identified and discussed on a multiprofessional basis. Results: Euriclea Project for care of CML patients with the description of a new and expanded nurse role was defined. The Nurse Case Manager or Nursing Clinical Experts were identified as key people for the management of the side effects of treatment, the promotion of the therapeutic adherence and the evaluation of efficacy and effectiveness of the process through the identification of specific indicators for structure, process and outcome. Discussion: The focal areas of the care process were identified so as to define a different approach to the CML patient, through a holistic view of care and the multidisciplinary interventions.